A comparative photocatalytic degradation study of cationic and anionic dyes using ZnIn2S4 photocatalyst. (1st March 2023) - Chand, Mool; Barthwal, Swapnil; Rawat, Arun Singh; Khanuja, Manika; Rawat, Seema
Abstract: Semiconductor mediated photocatalysis has emerged as a promising solution for dye degradation and environmental remediation. Zinc Indium Sulfide (ZnIn2 S4, ZIS) is a benign, eco-friendly, visible-light-responsive photocatalyst, exhibiting excellent optoelectronic properties. In this work, we present a scalable, low temperature and template-free chemical aqueous solution method for the synthesis of ZIS. The obtained powder sample was used for a comparative dye degradation study of cationic (Malachite green) and anionic (Congo red) dye. The higher photocatalytic efficiency of ZIS is due to the higher BET surface area (55.042 m 2 g −1 ) and low band gap (2.3 eV). Under Sunlight, almost 80 percent degradation occurs within 20 min of the experiment for both Malachite green (MG) and anionic Congo red (CR) dye, outperforming previously reported results. Scavenger studies were used to figure out the radicals involved in photocatalytic mechanics and to come up with viable photocatalytic degradation routes. The reusability and stability of ZIS were carried out up to the 5th cycles. Our result revealed that ZIS possesses high stability, reusability, and efficient potential to be an effective dye degradation photocatalyst.